Politicising the Amnesty: Struggles for Migrants' Legality during a Pandemic - Bonizzoni, Paola; Hajer, Minke (PARTECIPAZIONE E CONFLITTO, 2023)
The 2020 regularisation for irregular migrant workers in Italy relied extensively on civil society actors' (CSAs) involvement to provide information, legal support and handle the bureaucratic procedures of the programme. Based on qualitative research carried out with CSAs, migrants and employers involved in the programme, the article describes the heterogeneity of the CSAs involved as well as the different politicisation routes they followed. We show that, through a series of activities – information provision, preparing and sending applications, institutional lobbying and case advocacy, civil disobedience and protest – CSAs have attempted to repoliticise the amnesty through four different avenues: solidarity, debordering, empowering and contention.